El Teatro Bunraku: - Brazhnikova Tsybizova, Violetta (2022)
The object of this research work is one of the three great traditional genres of Japanese theatre, the Bunraku puppet theatre. Throughout this research, it is presented how and where the puppet theatre emerged in Japan, and the reasons why its structure changed substantially in the 18th century are observed. The circumstances surrounding the change of the name of this theatrical genre in the 19th century are also analyzed. As among scholars this theatrical genre is considered one of the sources of the Kabuki theatre, in this article the parallel development during the 17th and 18th centuries of the Bunraku puppet theatre and the Kabuki theatre, in which human performers are involved, is observed. For this reason, in this work both theatrical genres are mentioned and their similarities and the most outstanding differences between them are examined. Likewise, the figure of Chikamatsu Monzaemon, one of the most important playwrights on the Japanese scene, is briefly presented, and his influence in establishing the aesthetic values ​​that continue to govern puppet theater in the 21st century is delved into. Some of the similar manifestations in the field of the performing arts in Spain are also considered, and the influence that the Bunraku theatre has exerted on them is presented.